An Ultrastable Ionic Chemiresistor Skin with an Intrinsically Stretchable Polymer Electrolyte. Issue 20 (30th March 2018) - Jin, Ming Liang; Park, Sangsik; Kim, Jong‐Seon; Kwon, Sung Hyun; Zhang, Shuye; Yoo, Min Seok; Jang, Sungwoo; Koh, Hyeong‐Jun; Cho, Soo‐Yeon; Kim, So Young; Ahn, Chi Won; Cho, Kilwon; et al.
Abstract: Ultrastable sensing characteristics of the ionic chemiresistor skin (ICS) that is designed by using an intrinsically stretchable thermoplastic polyurethane electrolyte as a volatile organic compound (VOC) sensing channel are described. The hierarchically assembled polymer electrolyte film is observed to be very uniform, transparent, and intrinsically stretchable. Systematic experimental and theoretical studies also reveal that artificial ions are evenly distributed in polyurethane matrix without microscale phase separation, which is essential for implementing high reliability of the ICS devices. The ICS displays highly sensitive and stable sensing of representative VOCs (including toluene, hexane, propanal, ethanol, and acetone) that are found in the exhaled breath of lung cancer patients. In particular, the sensor is found to be fully operational even after being subjected to long‐term storage or harsh environmental conditions (relative humidity of 85% or temperature of 100 °C) or severe mechanical deformation (bending to a radius of curvature of 1 mm, or stretching strain of 100%), which can be an effective method to realize a human‐adaptive and skin‐attachable biosensor platform for daily use and early diagnosis. Abstract : An ultrastable performance of an ionic chemiresistor skin (ICS) sensor is created using intrinsically stretchable solid‐state polymer electrolyte. The ICS sensor displays highly sensitive and stable sensing of volatile organic compound gases even after being subjected to long‐term storage, harsh environmental conditions, or severe mechanical deformation, indicating its potential as a human‐adaptive, skin‐attachable biosensor platform.